The Study of Serum Vitamin D and Insulin Resistance in Chinese Populations with Normal Glucose Tolerance - Lin Ding; Congcong Wang; Heliang Ma; Yuling Tian; Yong Lu; Shuguang Pang (International Journal of Endocrinology)
Objectives. The aim of this study was to investigate the relationship between serum vitamin D and insulin resistance in Chinese subjects without diabetes mellitus. Methods. Serum 25(OH)D was measured in 897 individuals with normal glucose tolerance (NGT). Oral glucose tolerance tests (OGTTs) were conducted to exclude cases with diabetes, impaired fasting glucose (IFG), and impaired glucose tolerance (IGT). Metabolic parameters were measured and compared between the highest and lowest 25(OH)D quartiles. The relationship between serum 25(OH)D and homeostatic model assessment-insulin resistance (HOMA-IR) was analyzed. Results. Indexes, such as HOMA-IR, FINS, and SBP, were negatively correlated with serum 25(OH)D concentrations. Compared with the lowest quartile, individuals in the highest group had decreased Lg (HOMA-IR), Lg (FINS), and SBP. Pearson correlation analyses showed that serum 25(OH)D was negatively associated with age, BMI, Lg (HOMA-IR), and Lg (FINS). Multivariate linear regression analysis confirmed the negative correlation of Lg (HOMA-IR) and 25(OH)D. Conclusions. This study showed that serum 25(OH)D could be regarded as an independent predictor of insulin resistance for subjects without diabetes mellitus in China. Adequate vitamin D supplementation may improve multiple metabolic disturbances.